Building Organisational Resilience for the Construction Industy: Strategic Resilience Indicators. Issue 1 (November 2019) - Sapeciay, Zulkfli; Wilkinson, Suzanne; Costello, Seosamh B.; Adnan, Hamimah
Abstract: New Zealand has been affected by a number of natural disasters in recent years. One such example is the 2010 Christchurch earthquake that led to significant impacts to businesses, buildings and critical infrastructure. Construction organisations play an important role in reconstruction programs, and communities rely on their services, particularly post-disaster. Improving the resilience of construction organisations to natural disasters not only minimises the negative consequences to their organisations post-disaster and enhances their organisational performance during business as usual, but also helps to improve community resilience. However, very few studies have developed the concept of organizational resilience and none specifically in the construction sector. This paper identifies strategic resilience indicators for construction organizations. Triangulation analysis of the five studies, in-depth interviews and questionnaire surveys revealed leading indicators of organizational resilience which can help to develop a resilience framework for construction organizations. The findings suggest that the construction industry needs a framework that fosters resilience which itself can potentially enhance organisational capacity to recover quickly after a crisis or disaster.